Housing economics and public policy : essays in honour of Duncan Maclennan - O'Sullivan, Tony.; Gibb, Kenneth; Maclennan, Duncan; RICS Foundation (Oxford, UK ; Malden, MA, USA : Blackwell Science, 2003)
This book is a timely assessment of 20 years of progress in the field of housing economics and its application to policy and practice. Two decades on from the publication of Duncan Maclennan's influential Housing Economics, 16 leading housing experts - both academics and policy makers from across the world - now honour Maclennan's contributions. The chapters here present a contemporary survey of key issues in housing, from urban housing markets and sub-market modelling, to the economics of social housing, the basis for housing planning, economic analysis of neighbourhoods
1. Introduction / Tony O'Sullvan and Kenneth Gibb -- 2. Urban Housing Models / Kenneth Gibb -- 3. Segmentation, Adjustment and Disequilibrium / Yong Tu -- 4. Transactions Costs and Housing Markets / John M. Quigley -- 5. Hedonic Pricing Models: a Selective and Applied Review / Stephen Malpezzi -- 6. Housing, Random Walks, Complexity and the Macroeconomy / Geoffrey Meen -- 7. Taxation, Subsidies and Housing Markets / Gavin A. Wood -- 8. The Economics of Social Housing / Christine M.E. Whitehead -- 9. Neighbourhood Dynamics and Housing Markets / George C. Galster -- 10. Access to Home Ownership in the United States: the Impact of Changing Perspectives on Constraints to Tenure Choice / Joseph Gyourko -- 11. Planning Regulation and Housing Supply in a Market System / Glen Bramley -- 12. Economics and Housing Planning / Tony O'Sullivan -- 13. The Right to Buy in Britain / Nick Williams -- 14. The Political Economy of Housing Research / David Donnison and Mark Stephens -- 15. Policy and Academia: an Assessment / Richard Best.
"RICS Foundation"--Cover
Includes bibliographical references (pages 283-317) and index.
Print version record.
English.
John Wiley and Sons
Keywords: Housing policy; Housing; Housing policy -- Great Britain; Housing -- Great Britain; Logement -- Politique gouvernementale; Logement -- Politique gouvernementale -- Grande-Bretagne.; BUSINESS & ECONOMICS -- Real Estate -- General; Housing; Housing policy; Great Britain; Huisvesting; Huisvestingsbeleid; 4.240.; Politique du logement; Logement; Politique du logement -- Grande-Bretagne.; Logement -- Grande-Bretagne.; Festschriften; Festschriften